ALIH KODE DAN CAMPUR KODE DALAM INTERAKSI JUAL BELI DI PASAR JOHAR - Maduwani, Jasmine Sobhita; Yulianti, Wiwik; Yustanto, Henry (Universitas Sebelas Maret, 2024)
The problems in this research are (1) how is the form of code-switching and code-mixing used by traders with buyers in Johar market, Semarang City? (2) how is the function of code-switching and code-mixing used by the sellers with buyers in Johar market, Semarang City? (3) how is the background factor of code-switching and code-mixing used by sellers with buyers in Johar market, Semarang City? The purpose of this research is (1) to describe the form of code-switching and code-mixing that happened in Johar market, Semarang City (2) to describe the function of code-switching and code-mixing that happened in Johar market, Semarang City (3) to describe the background factors of code-switching and code-mixing that happened in Johar market, Semarang City. This type of research is basic research. The level of this research is descriptive qualitative research. The data of this research are the utterances containing code-switching and code-mixing spoken by sellers and buyers in Johar market. The data source of this research is informants, namely buyers and sellers in Johar market. The data collection method used in this research is the listening method, the basic technique of tapping with the further techniques of simak libat cakap, simak bebas libat cakap, record, and note. The method used to analyze this data is using agih method and padan method.